College education and wages in the UK: estimating conditional average structural functions in nonadditive models with binary endogenous variables - Tobias J. Klein (Institute for the Study of Labor (IZA), 2007)
We propose and implement an estimator for identifiable features of correlated random coefficient models with binary endogenous variables and nonadditive errors in the outcome equation. It is suitable, e.g., for estimation of the average returns to college education when they are heterogeneous across individuals and correlated with the schooling choice. The estimated features are of central interest to economists and are directly linked to the marginal and average treatment effect in policy evaluation. The advantage of the approach that is taken in this paper is that it allows for non-trivial selection patterns. Identification relies on assumptions weaker than typical functional form and exclusion restrictions used in the context of classical instrumental variables analysis. In the empirical application, we relate wage levels, wage gains from a college degree and selection into college to unobserved ability. Our results yield a deepened understanding of individual heterogeneity which is relevant for the design of educational policy.
urn:nbn:de:101:1-20080402134
Keywords: 330; Bildungsertrag; Mikroökonometrie; Nichtparametrisches Verfahren; Theorie; Großbritannien